Histologia do fígado de tilápia do Nilo (Oreochromis niloticus) alimentados com dietas contendo silagem biológica de pescado - Honorato, Claucia A.; da Cruz, Claudinei; Carneiro, Dalton J. [UNESP]; Machado, Márcia R.F. [UNESP]; Nascimento, Camila A.; Saturnino, Klaus C. (FapUNIFESP (SciELO), 2014)
This study aimed to evaluate possible histopathological liver of tilapia fed diets containing fish silage and level protein. Sample of 180 fed with tilapia fingerlings fed with diets containing three protein levels (20, 24 and 28% CP), and Proportions residue fermented silage of tilapia (1/4 and 1/2) of were analyzed during 75 days. The tissue fragments were fixed in Bouin and included in Histosec®. After that, between 2 to 5μm slices were done in a rotation microtome. The methods used for tissue analysis were hematoxilin/eosin and PAS. The histological slices were examined under light microscope (Olympus BX-50). The disarray in the morphology of the liver of fish fed biological silage was influenced by high protein levels, and increased proportions of 1/2 of animal protein diets. It was observed that the variation of hepatocytes is directly related to the type of diet for fish. In fish fed diets containing 28% CP, the liver showed disruption of the structure cordon of hepatocytes, necrosis and shifting points of the core to the periphery. Elevated levels of biological fish silage cause deleterious changes in the liver. The level of protein required to maintain the health of the associated development fish is 24% crude protein.
Histology liver in Nile tilapia (Oreochromis niloticus) fed diets with fish silage
Keywords: Fish silage; Hepatocytes; Liver histology; Nile tilapia; Oreochromis niloticus